Consumption, wealth, stock and government bond returns : international evidence - Afonso, António (2011)
In this paper, we show, from the consumer’s budget constraint, that the residuals of the trend relationship among consumption, aggregate wealth, and labour income should predict both stock returns and government bond yields. We use data for several OECD countries and find that when agents expect future stock returns to be higher, they will temporarily allow consumption to rise. Regarding government bond yields, when bonds are seen as a component of asset wealth, then investors react in the same way. If, however, the increase in the yields is perceived as signalling a future rise in taxes, then they will temporarily reduce their consumption.